Characterization of the mineral fracture mechanics to improve the efficiency in the grinding process in a concentrator plant - Basurto-Contreras, Cesar Marino; Vidal-Castañeda, Miguel Kedrov Spirkinte; Toykin-Mucha, Cesar Roberto; Carvo-Baltazar, Óscar Saúl; Ventocilla-Ruiz, Yasmine Leonila; León-Ayala, Ana Herlinda (Edelweiss Applied Science and Technology, 2025)
This study addresses the critical need for improving energy efficiency in the mineral comminution process, a key factor in the mining industry. Despite the extensive research on comminution, significant gaps remain in understanding how energy consumption can be optimized across different stages of the process. The objective of this research is to evaluate energy consumption patterns and identify strategies for enhancing energy efficiency in mineral processing, particularly focusing on ball mills. The methodology involved an analysis of operational data from a processing plant, including energy consumption rates, feed characteristics, and processing parameters. Key findings reveal that energy consumption in comminution is influenced by factors such as ore hardness, mill parameters, and the size reduction achieved. Furthermore, the study indicates a notable potential for reducing energy use by optimizing milling conditions and applying energy-efficient technologies. In conclusion, this research provides valuable insights for reducing energy consumption in the mining sector, with implications for sustainability, cost reduction, and environmental impact. Future studies should explore alternative technologies and further refine operational models to enhance energy efficiency in mining operations.